Ray Stannard Baker papers - Baker, Ray Stannard, 1870-1946.
Correspondence, diaries, journals, notebooks, drafts of books and articles, family papers, scrapbooks, clippings, and printed matter concerning Baker's career in newspaper and magazine writing especially with the Chicago Record and McClure's Magazine, his role in the Paris Peace Conference, and his family and early life. Subjects include progressivism, labor conditions, and development of industrialism. Papers collected by Baker for his biography of Woodrow Wilson consist of Wilson's correspondence including letters to Ellen Axson Wilson, interviews, and other material relating to Wilson and his family. Also includes a bibliography of Baker's writings, portions of the autobiography of Robert M. La Follette (1855-1925), and material relating to Baker's study of African Americans in the Progressive era, "Following the Color Line."
Correspondents include Jane Addams, Albert A. Boyden, Frank Nelson Doubleday, W.E.B. Du Bois, Ernst Heinrich Philipp August Haeckel, Norman Hapgood, Ben B. Lindsey, S.S. McClure, George Foster Peabody, John S. Phillips, Theodore Roosevelt, Upton Sinclair, Lincoln Steffens, Ida M. Tarbell, Booker T. Washington, William Allen White, Edith Bolling Galt Wilson, Woodrow Wilson, and Leonard Wood.
Microfilm edition available
Microfilm produced from originals in the Manuscript Division.
In part, photocopies and transcripts.
Library of Congress Prints and Photographs Division.
Library of Congress Geography and Map Division.
Journalist and author.
Keywords: Addams, Jane, -- 1860-1935 -- Correspondence; Boyden, Albert A. -- 1875-1925 -- Correspondence; Doubleday, Frank Nelson, -- 1862-1934 -- Correspondence; Du Bois, W. E. B. -- 1868-1963 -- Correspondence; Haeckel, Ernst, -- 1834-1919 -- Correspondence; Hapgood, Norman, -- 1868-1937 -- Correspondence; La Follette, Robert M. -- 1855-1925.; Lindsey, Ben B. -- 1869-1943 -- Correspondence; McClure, S. S. -- 1857-1949 -- Correspondence; Peabody, George Foster, -- 1852-1938 -- Correspondence; Phillips, John S. -- 1861-1949 -- Correspondence; Roosevelt, Theodore, -- 1858-1919 -- Correspondence; Sinclair, Upton, -- 1878-1968 -- Correspondence; Steffens, Lincoln, -- 1866-1936 -- Correspondence; Tarbell, Ida M. -- 1857-1944 -- Correspondence; Washington, Booker T., -- 1856-1915 -- Correspondence; White, William Allen, -- 1868-1944 -- Correspondence; Wilson, Edith Bolling Galt, -- 1872-1961 -- Correspondence; Wilson, Ellen Axson -- Correspondence; Wilson, Woodrow, -- 1856-1924.; Wilson, Woodrow, -- 1856-1924 -- Correspondence; Wood, Leonard, -- 1860-1927 -- Correspondence; Baker family; Wilson family; Chicago record; McClure's magazine; African Americans -- History; American newspapers -- Illinois -- Chicago; Industries -- United States; Journalism -- United States; Labor -- United States; Progressivism (United States politics); World War, 1914-1918 -- Peace; Authors; Journalists